ACTINIC GRANULOMA OF O’BRIEN – RESPONSE TO GRISEOFULVIN - Pelegrin Tonin, Carolina (2016)
Actinic granuloma of O’Brien, also called annular elastolytic giant cell granuloma is a rare condition. It shows clinically as papules lesions that converge in annular plaques lesions with an atrophic center. Histologically, it evidences elastophagocytosis and elastolysis. The case below describes a female patient, 53 years old, that had classical clinical and histopathological lesions of actinic granuloma that showed a significant improvement upon the introduction of adjunctive griseofulvin therapy.